A template for an improved rock-based subdivision of the pre-Cryogenian timescale - Shields, Graham A. (2022)
The geological timescale before 720 Ma uses rounded absolute ages rather than specific events recorded in rocks to subdivide time. This has led increasingly to mismatches between subdivisions and the features for which they were named. Here we review the formal processes that led to the current timescale, outline rock-based concepts that could be used to subdivide pre-Cryogenian time and propose revisions. An appraisal of the Precambrian rock record confirms that purely chronostratigraphic subdivision would require only modest deviation from current chronometric boundaries, removal of which could be expedited by establishing event-based concepts and provisional, approximate ages for eon-, era-and period-level subdivisions. Our review leads to the following conclusions: (1) the current informal four-fold Archean subdivision should be simplified to a tripartite scheme, pending more detailed analysis, and (2) an improved rock-based Proterozoic Eon might comprise a Paleoproterozoic Era with three periods (early Paleoproterozoic or Skourian, Rhyacian, Orosirian), Mesoproterozoic Era with four periods (Statherian, Calymmian, Ectasian, Stenian) and a Neoproterozoic Era with four periods ( pre-Tonian or Kleisian, Tonian, Cryogenian and Ediacaran). These proposals stem from a wide community and could be used to guide future development of the pre-Cryogenian timescale by international bodies.